PENGARUH PENAMBAHAN PENGAWET KARAGENAN TERHADAP KUALITAS OTAK-OTAK IKAN TENGGIRI (Scomberomorus commersoni) KULINER KEARIFAN LOKAL SEBAGAI RANCANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) PADA PEMBELAJARAN BIOTEKNOLOGI KONVENSIONAL DI SMA - Fenny Nadya Anggraeni; Imam Mahadi; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this research is to know about the effet of adding carrageenan preservatives to the quality of Mackerel’s Otak-otak of culinary local wisdom as a draft of the student worksheet (LKPD) in Biotechnology learning in High school. This research was conducted in March untill May 2019. This research uses a completely randomized design (RAL) with 5 treatments and 3 replications. The observed of parameters included Protein content, Fat contant and Hedonic test which is covering aspects of appearance, aroma and texture. The results showed that the addition of carrageenan had a significant effect on protein content and fat content in the Mackerel’s otak-otak (Scomberomorus commersoni) where the treatment of 2% carrageenan concentration was the best treatment for 9.97% of protein content and treatment of 1% carrageenan concentration was the best treatment for 1.12% of fat content. Where as in the organoleptic hedonic test, most favorited color and taste by the panelists are Mackerel’s otak-otak with addition of 2% carrageenan concentration. The result of this study are uses as a draft of Student Worksheets (LKPD) in the learning of conventional Biotechnology in the High School.Key Words: Carrageenan, Mackerel’s,Organoleptic,Otak-otak, Proksimat, WorksheetStudent (LKPD)